PERSEPSI RISIKO PENGEMBANG PERUMAHAN DI KABUPATEN BANYUMAS - Partamihardja, Basuki (Semarang State University, 2014)
This study aims to analyze the perceptions of developer and renovator on the probability and risk impact of housing development and response to risks that occur in the business of housing pengembangs . The study was conducted by distributing questionnaires to 30 respondents 30 respondents pengembangs and implementers in real estate development project in Banyumas. The analysis was performed based on the average value , probability - impact risk matrix. ANOVA test (F - test) to test the differences between groups of respondents pengembangs and implementers . The results of this study are: the risks that have a high probability and high impact are the financial risks and risk sales, the risks are rare and have a low impact is legal risk and political risk, the risk is often the case , but have a low impact is technical risk and risk management , the risk of a rare but has a high impact is the nature of risk. Responded by controlling the risk of sales through increased marketing, promotion and the selection of the right location. Technical risk and control management responded through contract clauses, control mechanisms and labor standards. Risk legality responded ceck risk aversion through legal documents. Risk responded political risk aversion through negotiation and socialization. Natural risks that climate and weather are responded to through planning control, whereas a natural disaster is a pure risk transfer of risk allocation responded with a third party such as an insurance. Financial risks such as rising prices responded to the acceptance of risk through a revision of the sales price.Penelitian ini bertujuan untuk menganalisis persepsipengembang dan pelaksana terhadap probabilitas dan dampak risiko pengembangan perumahan serta respon terhadap risiko yang terjadi pada usaha pengembang perumahan. Penelitian dilakukan dengan menyebarkan kuesioner terhadap 30 responden pengembang dan30 responden pelaksana pada proyek pembangunan perumahan di Kabupaten Banyumas.Analisis dilakukan berdasarkan nilai rata-rata, matriks probabilitas-dampak risiko. Uji Anava (F-test) untuk menguji ada tidaknya perbedaan antara kelompok responden pengembang dan pelaksana. Hasil yang didapat dari penelitian ini adalah: risiko yang mempunyai probabilitas tinggi dan dampak tinggi adalah risiko keuangan serta risiko penjualan, risiko yang jarang terjadi dan mempunyai dampak rendah adalah risiko legalitas dan risiko politik, risiko yang sering terjadi namun mempunyai dampak rendah adalah risiko teknis dan risiko manajemen, risiko yang jarang terjadi namun mempunyai dampak tinggi adalah risiko alam. Risiko penjualan direspon dengan pengendalian melalui peningkatan pemasaran, promosi serta pemilihan lokasi yang tepat. Risiko teknis dan manajemen direspon dengan pengendalian melalui klausul kontrak, mekanisme kontrol dan standar kerja. Risiko legalitas direspon dengan penghindaran risiko melalui ceck dokumen legalitas. Risiko politik direspon dengan penghindaran risiko melalui negosiasi dan sosialisasi. Risiko alam yaitu iklim dan cuaca direspon dengan pengendalian melalui perencanaan, sedangkan bencana alam merupakan risiko murni direspon dengan pengalihan risiko alokasi pihak ketiga seperti asuransi. Risiko keuangan seperti kenaikan harga-harga direspon dengan penerimaan risiko melalui revisi harga penjualan.